ERROR ANALYSIS OF KOREAN PARTICLE-PREDICATE COLLOCATION BY INDONESIAN SPEAKERS: ANALISIS KESALAHAN KOLOKASI PARTIKEL-PREDIKAT BAHASA KOREA PADA PENUTUR BAHASA INDONESIA - Daniel Rolis Cuajaya; Usmi Usman (Jurnal Kata, 2022)
This study discusses an analysis of Korean language particle-predicate collocation error made by Indonesian speakers. This study aims to analyze the error of using Korean particle-predicate collocations done by Indonesian speakers. This study is written to answer two questions; which types of particle-predicate collocation errors do Indonesian speakers make the most? and what are the forms of Korean particle-predicate collocation errors made by Indonesian speakers? This study uses both qualitative and quantitative methods and uses the results of questionnaires that had been distributed online as material of analysis. The data obtained was calculated and classified based on the type of error using language error analysis and types of language error theory. The result of this study shows that the highest type of error made by Indonesian speakers in the use of particle-predicate collocation is substitution error (48.47%), followed by omission error (33.05%) and addition error (18.48%). Furthermore, the error of using nominative case particle-predicate collocations (39.47%) is highest types of error made by Indonesian speakers, followed by error in the use of object case particle-predicate collocations (30.30%) and error in the use of adverbial case particle-predicate collocations (30.23%).